Nighttime Cooling of an Urban Pond - Solcerova, Anna; van de Ven, Frans; van de Giesen, Nick (Frontiers in Earth Science, 2019)
One of the processes by which open water cools the air during hot summer days is by storing the heat and increasing its own temperature. This heat is then released at night. The aim of this paper is to analyze this cooling process by quantifying the magnitude of turbulent, latent and sensible, heat fluxes in comparison to radiative and ground fluxes. A detailed vertical temperature profile was measured in an urban pond (~70 cm deep with surface area of 3,627 m2) in Delft (NL) using Distributed Temperature Sensing for a period of one month. The results show that, from the total of 2.7 MJm−2 of heat released by the pond on an average summer night, 43% of the thermal energy is emitted as longwave radiation, 39% as latent energy, and only 11% as sensible heat. An additional 0.10–0.32 MJm−2 is transferred into the bottom of the lake. Temperature distribution and cooling of the water profile is influenced by weather conditions during the preceding day. This paper provides an insight into a behavioral pattern of an urban pond at night. The results can shed some light into the potential of urban bodies to increase the air temperature of their surroundings at night.